Legal and Policy Considerations for Assigning Price Stabilization of Basic Materials to Regional-Owned Enterprises - Muttaqien, Mirza; Widyaningrum, Sigmawati; Muhammad, Zati Rizqi (Airlangga Journal of Innovation Management, 2024)
Annual inflation in July 2022 will be the highest since October 2015. High inflation can cause people's real income to continue to erode because the price of goods is increasingly expensive. To create a stable regional economy and affordable people's purchasing power, the Governor of East Java issued Governor Regulation 58 of 2022 concerning the Assignment to PT Jatim Grha Utama to Implement Price Stabilization of Basic Necessities through East Java Food Granary Activities. This research aims to analyze the legal and policy considerations of the East Java Food Barn. It is hoped that the results of this research will affect regional governments in taking policies to deal with inflation. The type of research used in this paper is the socio-legal research method. The results showed that in Article 45 of the Trade Law, Regional Governments control the accessibility of fundamental necessities and/or vital products all through the domain of the Unitary State of the Republic of Indonesia in satisfactory amounts, great quality, and reasonable costs. Law is an important component in the welfare reform process. The East Java Food Granary Program was implemented as an effort to control inflation and purchasing power, so the East Java Food Barn program was implemented in 8 East Java IHK Regency/City areas, to be precise at 25 market points based on the SBH carried out by BPS in 2018.